PNLSS Toolbox 1.0⁎This work was supported by the Flemish fund for scientific research FWO under license number G0068.18N. Issue 7 (2021) - Decuyper, Jan; Tiels, Koen; Schoukens, Johan
Abstract: This is a demonstration of the PNLSS Toolbox 1.0. The toolbox is designed to identify polynomial nonlinear state-space models from data. Nonlinear state-space models can describe a wide range of nonlinear systems. An illustration is provided on experimental data of an electrical system mimicking the forced Duffing oscillator, and on numerical data of a nonlinear fluid dynamics problem.